MEDIA DAN DAKWAH MODERASI: MELACAK PERAN STRATEGIS DALAM MENYEBARKAN FAHAM MODERASI DI SITUS NAHDLATUL WATHAN ONLINE SITUS KALANGAN NITIZEN MUSLIM-SANTRI - FAHRURROZI FAHRURROZI; MUHAMMAD THOHRI (Universitas Islam Negeri (UIN) Mataram, 2019)
Islamic moderation is positioned as mainstream in NW online media. This mainstreaming needs to be developed into a more comprehensive study to carry out a constructive role in all its components. One important component is the media content. In the aspect of content, especially Islamic moderating da'wah content can at least be developed through the formulation of the principles of developing on-line media that are extracted from the principle of moderation and the use of an appropriate approach in integrating moderation propaganda content. Netizens are far more effective when using social media such as the Nahdlatul Wathan website that is read and seen by thousands and even through millions of readers and users. The most progressive finding from this study is the massive awareness of netizens, especially millennial students, to recognize the content of da'wah that is soothing and inspiring. Thus, the perception of netizens of students about social media does not always neglect themselves as santri but can increase their capacity building to continue to be creative and to make achievements through media literacy.